Flame-retardant phase-change aerogel for inhibiting spreading of thermal runaway of lithium battery and preparation method of flame-retardant phase-change aerogel
Phase change aerogels were prepared by a one-step freeze-drying method and coated with flame-retardant coatings. This solved the problems of leakage and high thermal conductivity of phase change aerogels, achieving a highly efficient suppression effect on thermal runaway of lithium batteries and exhibiting excellent heat insulation and flame-retardant properties.
Patent Information
- Application Number
- CN202510727991.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-11-04
AI Technical Summary
In existing technologies, phase change aerogels have leakage problems in lithium batteries, and commonly used barrier layer materials fail to significantly reduce thermal conductivity when suppressing the spread of thermal runaway, thus failing to effectively block heat conduction.
Phase change aerogels were prepared by a one-step freeze-drying method, and a flame-retardant layer was formed on their surface by soaking and coating with a flame-retardant coating. A composite coating of ammonium polyphosphate, dipentaerythritol and silica aerogel was used to form a heat insulation enhancer, thus preparing a flame-retardant phase change aerogel with both phase change energy storage and heat insulation functions.
It effectively prevents leakage of phase change aerogel during long-term use, has excellent heat insulation and flame retardant properties, significantly reduces thermal conductivity, and can effectively suppress the spread of thermal runaway in lithium batteries.
Smart Images

Figure CN120888110A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of battery thermal runaway, in particular to a flame-retardant phase change aerogel for inhibiting the spread of lithium battery thermal runaway and a preparation method thereof. BACKGROUND
[0002] Lithium ion batteries are widely used in key fields such as new energy vehicles, aerospace and energy storage power stations due to their high energy density, long cycle life, low self-discharge rate and no memory effect, etc., providing stable power output for various equipment. However, in lithium battery systems, battery cells are usually designed in a compact arrangement. Although this highly integrated structure can improve energy density, it also hides a huge safety hazard. Once a battery cell experiences thermal runaway, the high energy density chemical energy stored inside will be instantly converted into a large amount of heat energy, which will rapidly transfer to adjacent battery cells through radiation, conduction and convection, etc., triggering a destructive chain reaction of thermal runaway. This not only causes devastating damage to the battery pack itself, but also poses a serious threat to personal safety and public property, causing major safety accidents such as fires and explosions, so it is of great significance to inhibit lithium ion battery thermal runaway.
[0003] Current technologies for inhibiting the spread of lithium battery thermal runaway mainly fall into two categories: active protection and passive protection. Active protection technology relies on the battery management system to monitor key parameters such as battery temperature, voltage, current, etc. in real time. When the system detects abnormal conditions in the battery, it will quickly take measures such as power-off, starting the cooling device, spraying fire extinguishing agent, etc. to prevent the thermal runaway from worsening in the early stage. However, this technology highly depends on high-reliability sensors, controllers and communication links. Once the hardware fails, the protection capability may be lost; in addition, for thermal runaway directly caused by mechanical abuse such as collision and puncture, the active system often fails to respond quickly due to delay. Passive protection technology does not require external power or control systems, but rather builds inherent safety mechanisms inside or outside the battery to slow down or block the spread of thermal runaway. In a battery pack, heat conduction through the battery shell is considered the main way of thermal runaway spread, so placing a barrier layer in the battery pack to inhibit rapid heat conduction is the most commonly used method in passive protection strategies.
[0004] The commonly used barrier layer includes ceramic fiber and aerogel, etc. which have low thermal conductivity and flame-retardant effect. When placed in the middle of the battery pack, it can delay the spread of heat and extend the time for personnel to escape, reducing the impact of the accident when the battery experiences thermal runaway. However, according to the principle of heat conservation, the energy released by the thermal runaway battery is only constrained within the battery module, and over time, it may still cause thermal runaway in adjacent batteries, leading to the spread of thermal runaway within the battery pack.
[0005] A preparation method and application of an aerogel composite phase change thermal insulation material are disclosed in Chinese invention patent CN117964939B. The method loads polyethylene glycol 4000-6000 phase change material on modified cellulose aerogel, which is beneficial to enhancing the phase change performance of the aerogel composite phase change thermal insulation material. However, the preparation process is to first prepare aerogel, and then adsorb the phase change material into the aerogel, which will cause part of the phase change material to be adsorbed on the surface of the aerogel, resulting in uneven adsorption. In addition, since the phase change material completely fills the pores of the aerogel, the pore framework of the aerogel will indirectly provide a heat transfer path, and the thermal conductivity coefficient cannot be significantly reduced. Moreover, if the method of first preparing aerogel and then adsorbing phase change material into the aerogel is used, the polyvinyl alcohol aerogel cannot well adsorb the octadecanol phase change material, and the problem of leakage still exists. SUMMARY
[0006] In view of the problems existing in the prior art, the purpose of the present application is to provide a flame-retardant phase change aerogel for inhibiting the spread of thermal runaway of lithium batteries, which can effectively prevent the leakage problem of phase change aerogel during long-term use, has excellent thermal insulation performance, and has the dual functions of phase change energy storage and thermal insulation.
[0007] To achieve the above-mentioned purpose of the application, the following technical solutions are adopted: A preparation method of a flame-retardant phase change aerogel for inhibiting the spread of thermal runaway of lithium batteries, comprising the following steps: (1) Dissolve a polysaccharide emulsifier in deionized water, add octadecanol and stir uniformly, heat to 75-80°C until the octadecanol is in a molten state, and then stir uniformly to obtain an emulsion; (2) Dissolve polyvinyl alcohol in deionized water, stir at 90-95°C until the polyvinyl alcohol is completely dissolved, then add the emulsion and stir uniformly to obtain a mixed solution; (3) Pour the mixed solution into a mold, freeze-dry directly after multiple cycles of freeze-thaw to obtain a phase change aerogel; (4) Add ammonium polyphosphate, dipentaerythritol, and silica aerogel to silicone resin, stir uniformly to obtain a flame-retardant coating, immerse the phase change aerogel in the flame-retardant coating, take it out, and then cure at 100-160°C to obtain a flame-retardant phase change aerogel.
[0008] To further achieve the purpose of the present application, preferably, in step (1), the polysaccharide emulsifier is one or more of xanthan gum, nanocellulose, carboxymethyl cellulose, starch, and chitosan; and the mass ratio of the polysaccharide emulsifier, deionized water, and octadecanol is 1:50-150:5-20.
[0009] Preferably, in step (1), the stirring time for heating until octadecanol is in a molten state and then stirring until uniform is reached is 2-3 h; the stirring time for adding octadecanol is 2-3 h.
[0010] Preferably, in step (2), the mass ratio of polyvinyl alcohol to deionized water is 1:5~15; the mass ratio of polyvinyl alcohol solution to emulsion is 1:1~3; and the time for constant temperature stirring until polyvinyl alcohol is completely dissolved is 2~3 h.
[0011] Preferably, in step (3), the cyclic freeze-thaw operation is as follows: first freeze at a freezing temperature of -20~-10℃ for 8~16 h, and then thaw at room temperature for 4~8 h, and the number of cyclic freeze-thaw operations is 2~4 times.
[0012] Preferably, in step (3), the mold is a silicone mold; the freeze-drying time is 48-72 h; and the vacuum degree of freeze-drying is 5-25 Pa.
[0013] Preferably, in step (4), the mass ratio of the organosilicon resin, silica aerogel, ammonium polyphosphate, and dipentaerythritol is 52:16:6~10:2~6.
[0014] Preferably, in step (4), the soaking time is 30~60 s; the curing time is 8~12 h.
[0015] Preferably, in steps (1), (2) and (4), the stirring device is a constant temperature water bath, and the stirring speed is 600~800 r / min.
[0016] A flame-retardant phase change aerogel for suppressing the spread of thermal runaway in lithium batteries is prepared by the above-described method.
[0017] Compared with the prior art, the present invention has the following advantages: Traditional methods for preparing phase change aerogels typically involve a two-step process: first, freeze-drying to obtain the aerogel carrier material, and then loading the phase change material onto the aerogel via melt impregnation or vacuum impregnation. This invention, however, requires only a single freeze-drying step to load a phase change material with highly efficient heat absorption capacity onto the aerogel, successfully preparing a phase change aerogel with both phase change energy storage and thermal insulation functions.
[0018] This invention directly obtains phase change aerogels through freeze-drying. During this process, ice crystal sublimation leaves a porous structure. On one hand, the thermal conductivity of air within these pores is much lower than that of the solid material; on the other hand, the presence of pores causes discontinuous heat conduction paths. Therefore, the phase change aerogel of this invention has an even lower thermal conductivity of 0.0725 W·m. -1 ·K-1 , and can exhibit excellent thermal insulation performance.
[0019] The soaking coating process adopted by the present application is that a composite coating composed of a flame retardant and a thermal insulation enhancer is soaked and coated on the surface of the phase change aerogel to form a flame retardant layer, which not only effectively reduces the combustion-supporting risk of the material in the battery thermal runaway scenario, but also further prevents the leakage of the phase change aerogel during long-term use. Compared with other methods of directly incorporating a flame retardant into the structure, the soaking coating method does not have a great impact on the phase change enthalpy of the material, and the amount of the flame retardant is less.
[0020] 4、The preparation process of the present application is simple and easy to operate, and the prepared flame-retardant phase change aerogel has low thermal conductivity, high phase change latent heat and good flame-retardant effect, which can effectively delay or inhibit the thermal runaway spread of lithium ion batteries. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 It is a scanning electron microscope image of the cross section of the phase change aerogel prepared in Example 1 of the present application.
[0022] Figure 2 It is a differential scanning calorimetry graph of the phase change aerogel prepared in Example 1 of the present application.
[0023] Figure 3 It is a vertical combustion test graph of the flame-retardant phase change aerogel prepared in Example 1 of the present application and the phase change aerogel prepared in Comparative Example 1.
[0024] Figure 4 It is a schematic diagram of the thermal runaway spread test assembly of lithium ion battery packs.
[0025] Figure 5 It is a data graph of the thermal runaway spread test of lithium ion battery packs without inserting a barrier material.
[0026] Figure 6 It is a data graph of the thermal runaway spread test of lithium ion battery packs inserted with 5 mm thick flame-retardant phase change aerogel prepared in Example 1. DETAILED DESCRIPTION
[0027] In order to better understand the present application, the present application will be further described below in conjunction with the drawings and specific embodiments, but the embodiments of the present application are not limited thereto. The described embodiments are part of the embodiments of the present application, but not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0028] The present application provides a flame-retardant phase change aerogel for inhibiting the spread of thermal runaway of lithium batteries, which effectively prevents the leakage of phase change aerogel during long-term use, has excellent thermal insulation performance, and has the dual functions of phase change energy storage and thermal insulation.
[0029] Therefore, the present application provides a preparation method of a flame-retardant phase change aerogel for inhibiting the spread of thermal runaway of lithium batteries, which comprises the following steps: (1) Dissolve a polysaccharide emulsifier in deionized water, add octadecanol and stir until uniform, heat to 75-80°C until the octadecanol is in a molten state, and then stir until uniform to obtain an emulsion; (2) Dissolve polyvinyl alcohol in deionized water, stir at 90-95°C until the polyvinyl alcohol is completely dissolved, add the emulsion, and stir until uniform to obtain a mixed solution; (3) Pour the mixed solution into a mold, freeze-dry directly by multiple cycles of freezing and thawing to obtain a phase change aerogel; (4) Add ammonium polyphosphate, dipentaerythritol, and silica aerogel to silicone resin, stir until uniform to obtain a flame-retardant coating, soak the phase change aerogel in the flame-retardant coating, take it out, and cure at 100-160°C to obtain a flame-retardant phase change aerogel.
[0030] Since similar aerogels and flame-retardant coatings have related technical measures in the prior art, the amount of raw materials involved can be preferably obtained in combination with the purpose of the present application. In the above preparation method, the present application effectively utilizes the characteristics of octadecanol as a phase change material, especially the combination of octadecanol and polyvinyl alcohol, and the multiple cycles of freezing and thawing to prepare an aerogel. The phase change material with high heat absorption capacity is loaded onto the aerogel, and a phase change aerogel with dual functions of phase change energy storage and thermal insulation is successfully prepared. The pore structure of the polyvinyl alcohol aerogel can be seen from the scanning electron microscope image, and the octadecanol particles are firmly embedded in the pore framework of the aerogel. When the temperature exceeds the phase change temperature point, these pores will restrict the flow of octadecanol, and the phase change aerogel will not appear liquid leakage on the surface. And due to the rich pore structure inside the phase change aerogel, the heat transfer path is effectively blocked, and the heat conduction rate is reduced, so that the thermal conductivity coefficient of the phase change aerogel is only 0.0582-0.0637 W·m -1 ·K -1 .
[0031] The present application is a composite coating composed of a flame retardant and a thermal insulation enhancer, which forms a flame retardant layer on the surface of the phase change aerogel by immersion coating. It not only effectively reduces the risk of combustion of the material in the battery thermal runaway scenario, but also further prevents the leakage of the phase change aerogel during long-term use. Compared with other methods of directly incorporating flame retardants into the structure, the immersion coating method has little effect on the phase change enthalpy of the material, and the amount of flame retardant used is less. This idea is difficult to learn from existing technology. Embodiment
[0032] In step 1, 1 part of xanthan gum emulsifier was added to 100 parts of deionized water, stirred at a stirring speed of 600 r / min at room temperature for 2 h, then 20 parts of octadecanol was added, heated to a molten state at 75℃, then stirred at a stirring speed of 800 r / min at 75℃ for 2 h to obtain a phase change emulsion. In step 1, 1 part of xanthan gum emulsifier was added to 100 parts of deionized water, stirred at a stirring speed of 600 r / min at room temperature for 2 h, then 20 parts of octadecanol was added, heated to a molten state at 75℃, then stirred at a stirring speed of 800 r / min at 75℃ for 2 h to obtain a phase change emulsion. In step 1, 1 part of xanthan gum emulsifier was added to 100 parts of deionized water, stirred at a stirring speed of 600 r / min at room temperature for 2 h, then 20 parts of octadecanol was added, heated to a molten state at 75℃, then stirred at a stirring speed of 800 r / min at 75℃ for 2 h to obtain a phase change emulsion.
[0033] In step 1, 1 part of xanthan gum emulsifier was added to 100 parts of deionized water, stirred at a stirring speed of 600 r / min at room temperature for 2 h, then 20 parts of octadecanol was added, heated to a molten state at 75℃, then stirred at a stirring speed of 800 r / min at 75℃ for 2 h to obtain a phase change emulsion. Embodiment
[0034] In step 1, 1 part of xanthan gum emulsifier was added to 100 parts of deionized water, stirred at a stirring speed of 600 r / min at room temperature for 2 h, then 20 parts of octadecanol was added, heated to a molten state at 75℃, then stirred at a stirring speed of 800 r / min at 75℃ for 2 h to obtain a phase change emulsion. In step 1, 1 part of xanthan gum emulsifier was added to 100 parts of deionized water, stirred at a stirring speed of 600 r / min at room temperature for 2 h, then 20 parts of octadecanol was added, heated to a molten state at 75℃, then stirred at a stirring speed of 800 r / min at 75℃ for 2 h to obtain a phase change emulsion. The mixed solution was transferred to a customized silica gel mold, and was subjected to 3 freeze-thaw cycle treatments: first frozen at -20℃ for 10 h, and then thawed at 25℃ for 4 h. Finally, the sample was freeze-dried for 48 h to obtain the phase change aerogel material; In weight parts, 8 parts of silica aerogel, 5 parts of ammonium polyphosphate and 3 parts of dipentaerythritol were added to 26 parts of silicone resin to obtain a flame-retardant coating. The phase change aerogel was soaked in the flame-retardant coating for 40 s, then taken out and dried and cured in an oven at 140℃ for 9 h. After the end, the flame-retardant phase change aerogel was obtained. Example
[0035] In weight parts, 1 part of carboxymethyl cellulose emulsifier was added to 120 parts of deionized water, and stirred at a stirring speed of 800 r / min at room temperature for 2.5 h. Then 15 parts of octadecanol was added and heated to a molten state at 80℃. Then constant temperature stirring was carried out at 800 r / min at 80℃ for 2.5 h to obtain a phase change emulsion; In weight parts, 1 part of polyvinyl alcohol was added to 15 parts of deionized water, and constant temperature stirring was carried out at 800 r / min at 95℃ for 2.5 h to obtain a polyvinyl alcohol solution. Then according to a mass ratio of 1:2, 2 parts of the phase change emulsion obtained in step (1) was added to 1 part of the polyvinyl alcohol solution, and stirring was carried out at a stirring speed of 600 r / min at room temperature for 2.5 h to obtain a mixed solution; The mixed solution was transferred to a customized silica gel mold, and was subjected to 3 freeze-thaw cycle treatments: first frozen at -20℃ for 10 h, and then thawed at 25℃ for 4 h. Finally, the sample was freeze-dried for 48 h to obtain the phase change aerogel material; In weight parts, 8 parts of silica aerogel, 5 parts of ammonium polyphosphate and 3 parts of dipentaerythritol were added to 26 parts of silicone resin to obtain a flame-retardant coating. The phase change aerogel was soaked in the flame-retardant coating for 40 s, then taken out and dried and cured in an oven at 140℃ for 9 h. After the end, the flame-retardant phase change aerogel was obtained. Example
[0036] In weight parts, 1 part of carboxymethyl cellulose emulsifier was added to 120 parts of deionized water, and stirred at a stirring speed of 800 r / min at room temperature for 2.5 h. Then 15 parts of octadecanol was added and heated to a molten state at 80℃. Then constant temperature stirring was carried out at 800 r / min at 80℃ for 2.5 h to obtain a phase change emulsion; The polyvinyl alcohol was added to 9 parts of deionized water in a weight ratio of 1:9, and constant temperature stirring was carried out at 95°C and a stirring speed of 600 r / min for 3 h to obtain a polyvinyl alcohol solution. Then, 1 part of the polyvinyl alcohol solution was added to 3 parts of the phase change emulsion obtained in step (1) according to a mass ratio of 1:3, and stirring was carried out at room temperature and a stirring speed of 600 r / min for 3 h to obtain a mixed solution. The mixed solution was transferred to a customized silica gel mold, and three freeze-thaw cycle treatments were performed: first, freezing at -10°C for 8 h, and then thawing at 25°C for 8 h. Finally, the sample was freeze-dried for 72 h to obtain a phase change aerogel material. The flame-retardant coating was obtained by stirring 20 parts of silica aerogel, 12 parts of ammonium polyphosphate, and 3 parts of dipentaerythritol in 65 parts of silicone resin. The phase change aerogel was soaked in the flame-retardant coating for 60 s, then taken out and dried and cured in an oven at 160°C for 11 h. After the end of the process, a flame-retardant phase change aerogel was obtained.
[0037] Comparative Example 1 (without a flame-retardant layer) The xanthan gum emulsifier was added to 100 parts of deionized water in a weight ratio of 1:100, and stirring was carried out at room temperature and a stirring speed of 600 r / min for 2 h. Then, 20 parts of octadecanol was added and heated to a molten state at 75°C. Then, constant temperature stirring was carried out at 75°C and a stirring speed of 800 r / min for 2 h to obtain a phase change emulsion. The polyvinyl alcohol was added to 9 parts of deionized water in a weight ratio of 1:9, and constant temperature stirring was carried out at 95°C and a stirring speed of 600 r / min for 2 h to obtain a polyvinyl alcohol solution. Then, 1 part of the polyvinyl alcohol solution was added to 1 part of the phase change emulsion obtained in step (1) according to a mass ratio of 1:1, and stirring was carried out at room temperature and a stirring speed of 600 r / min for 2 h to obtain a mixed solution. The mixed solution was transferred to a customized silica gel mold, and three freeze-thaw cycle treatments were performed: first, freezing at -20°C for 12 h, and then thawing at 25°C for 6 h. Finally, the sample was freeze-dried for 48 h to obtain a phase change aerogel material.
[0038] Figure 1 The scanning electron microscope image of the cross section of the phase change aerogel prepared in Example 1 of the present application (i.e., Comparative Example 1) is shown in FIG. 1. Figure 1 As shown in FIG. 1, the pore structure of the polyvinyl alcohol aerogel can be seen, and the octadecanol particles are firmly embedded in the pore framework of the aerogel. Therefore, when the temperature reaches above the phase change temperature point, the pores will restrict the flow of octadecanol, and the phase change aerogel will not appear to have liquid leakage. Moreover, the rich pore structure inside the phase change aerogel effectively blocks the heat transfer path, reducing the heat conduction rate, so that the thermal conductivity of the phase change aerogel is only 0.0725 W·m-1 ·K -1 .
[0039] Figure 2 The differential scanning calorimetry diagram of the phase change aerogel prepared in Example 1 is directly measured by using a differential scanning calorimeter (DSC). As shown in FIG. 2, the melting temperature of the phase change aerogel prepared in Example 1 is 58℃, and the latent heat of phase change is 242.5 J / g, indicating that the prepared phase change aerogel has a high heat storage density. Figure 2
[0040] The phase change aerogels prepared in other examples are basically similar to the example, and the scanning electron microscope diagrams and the differential scanning calorimetry diagrams are not provided one by one.
[0041] Figure 3 The vertical combustion test diagram of the flame-retardant phase change aerogel prepared in Example 1 and the phase change aerogel prepared in Comparative Example 1. As can be seen, the phase change aerogel prepared in Comparative Example 1 can be easily ignited, and after ignition, the fire is rapid and the combustion is intense, and the flame will not be extinguished until the material is completely burned. The flame-retardant phase change aerogel prepared in Example 1 is ignited by a fire gun, and the flame will be extinguished within a few seconds after the fire gun is removed. Even if the material is ignited again with a fire gun, it is difficult to continue to burn. This is because the ammonium polyphosphate in the coating can release phosphoric acid as an acid source, and the dipentaerythritol acts as a carbon source to promote the formation of a carbon layer under the action of phosphoric acid, and the two cooperate to quickly form a carbon layer on the surface of the material with good heat insulation and oxygen insulation performance. The silica aerogel further hinders heat transfer, oxygen entering and combustible gas escaping due to its low thermal conductivity, physical barrier effect, etc., and its role in inhibiting thermal decomposition and capturing free radicals cooperates with ammonium polyphosphate and dipentaerythritol to improve the flame-retardant performance of the material. In addition, the non-combustible gases produced by the decomposition of the three together dilute the oxygen and combustible gas concentration in the combustion area, enhancing the flame-retardant effect. And from Table 1, a high oxygen index indicates that the material is not easy to burn, and a low oxygen index indicates that the material is easy to burn. The phase change aerogel prepared in Comparative Example 1 is a flammable material, while the flame-retardant performance of the flame-retardant phase change aerogels prepared in Examples 1, 2, 3 and 4 is greatly enhanced, rising to the level of difficult-to-burn materials.
[0042] The flame-retardant level in Table 1 is obtained according to the results of the vertical combustion test, and the LOI is measured by using a limiting oxygen index instrument.
[0043] Table 1 Figure 4 Schematic diagram of thermal runaway propagation test for lithium ion battery. Four square batteries with a capacity of 51 Ah are placed side by side, and a heating plate with a power of 300 W is placed on the left side of the leftmost battery. A stainless steel custom clamp is used to fix the test battery and heating plate, and heat insulation cotton is placed inside the clamp to reduce the heat dissipation of the battery to the clamp, affecting the test results. A K-type thermocouple with a diameter of 1 mm is attached to the center of the front and rear surfaces of each battery to record the temperature changes of the battery.
[0044] In order to test the ability of the flame-retardant phase change aerogel prepared in Example 1 to inhibit the thermal runaway propagation of lithium batteries, a thermal runaway propagation test of lithium ion batteries was conducted, and a blank control test was also conducted. Figure 5 Data graph of thermal runaway propagation test for lithium ion battery without inserting barrier material. Eight curves correspond to the front and rear plate center temperatures of the first, second, third, and fourth batteries in order of temperature rise. It can be seen that thermal runaway occurred in the four batteries in turn, and the thermal runaway propagation time between the batteries was not more than 2 min, and the propagation was very rapid. While Figure 6 Data graph of thermal runaway propagation test for lithium ion battery inserted with 5 mm thick flame-retardant phase change aerogel prepared in Example 1. From the graph, it can be seen that only the first battery experienced thermal runaway. This is because the flame-retardant phase change aerogel prepared in Example 1 was placed between the first and second batteries. When the temperature rises, the coating on the surface of the flame-retardant phase change aerogel carbonizes, blocking oxygen and some heat, so that the flames from the first battery do not affect the second battery. Then part of the phase change material melts and vaporizes to consume part of the heat. Then, due to the low thermal conductivity of the material itself, it is difficult for heat to transfer from the first battery to the second battery, resulting in a temperature of only 193°C on the front plate of the second battery after experiencing a temperature rise of 264 s, and then a decrease. Therefore, the second battery also did not experience thermal runaway.
[0045] In summary, in order to solve the problem of thermal runaway and its propagation of lithium ion batteries, the present application proposes to use flame-retardant phase change aerogel to block the propagation of battery thermal runaway. The present application first directly prepares a shape-stable phase change aerogel with octadecanol as the phase change core and polyvinyl alcohol aerogel as the skeleton by freeze-drying, and coats a flame-retardant layer to prepare a flame-retardant aerogel. The flame-retardant phase change aerogel of the present application has a high energy density and a low thermal conductivity (0.0582~0.0637 W·m -1 ·K -1 ), and good flame-retardant performance. The thermal runaway of an unprotected battery pack can spread to adjacent batteries within 2 min, while the flame-retardant phase change aerogel can successfully prevent the propagation of thermal runaway. Therefore, the flame-retardant phase change aerogel prepared by the present application can be applied to a battery thermal protection system.
[0046] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than limit them; although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that the technical solutions recorded in the foregoing embodiments can still be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a flame-retardant phase change aerogel for suppressing the spread of thermal runaway in lithium batteries, characterized in that... Includes the following steps: (1) Dissolve the polysaccharide emulsifier in deionized water, add octadecanol and stir until homogeneous, heat at 75~80℃ until octadecanol is in a molten state and stir until homogeneous to obtain an emulsion; (2) Dissolve polyvinyl alcohol in deionized water, stir at 90~95℃ until the polyvinyl alcohol is completely dissolved, add the emulsion, stir evenly to obtain a mixed solution; (3) Pour the mixed solution into a mold, and then freeze-dry it in one step to directly obtain phase change aerogel by repeatedly freezing and thawing. (4) Add ammonium polyphosphate, dipentaerythritol and silica aerogel to organosilicon resin, stir evenly to obtain flame retardant coating, soak the phase change aerogel in flame retardant coating and take it out, and cure it at 100~160℃ to obtain flame retardant phase change aerogel.
2. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (1), the polysaccharide emulsifier is one or more of xanthan gum, nanocellulose, carboxymethyl cellulose, starch, and chitosan; the mass ratio of the polysaccharide emulsifier, deionized water, and octadecyl alcohol is 1:50~150:5~20.
3. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (1), the stirring time for heating until octadecanol is in a molten state and then stirring until uniform is reached is 2-3 h; the stirring time for adding octadecanol is 2-3 h.
4. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (2), the mass ratio of polyvinyl alcohol to deionized water is 1:5~15; the mass ratio of polyvinyl alcohol solution to emulsion is 1:1~3; and the time for constant temperature stirring until polyvinyl alcohol is completely dissolved is 2~3 h.
5. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (3), the cyclic freeze-thaw operation is as follows: first freeze at a freezing temperature of -20~-10℃ for 8~16h, and then thaw at room temperature for 4~8h. The number of cyclic freeze-thaw operations is 2~4 times.
6. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (3), the mold is a silicone mold; the freeze-drying time is 48-72 h; and the vacuum degree of freeze-drying is 5-25 Pa.
7. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (4), the mass ratio of the organosilicon resin, silica aerogel, ammonium polyphosphate, and dipentaerythritol is 52:16:6~10:2~6.
8. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In step (4), the soaking time is 30~60 s; the curing time is 8~12 h.
9. The method for preparing flame-retardant phase change aerogel for suppressing thermal runaway propagation in lithium batteries according to claim 1, characterized in that, In steps (1), (2) and (4), the stirring device is a constant temperature water bath, and the stirring speed is 600~800 r / min.
10. A flame-retardant phase change aerogel for suppressing the propagation of thermal runaway in lithium batteries, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.
Citation Information
Patent Citations
Preparation method and application of aerogel composite phase change thermal insulation material
CN117964939B